The Effect of Planting Standards and Methods on The Field Fertility and Viability of Millet - Uzakov Gulomjon Okbutaevich; Kodirov Akhmadjon Abduraufovich; Muradov Rustam Zakirjanovich (Scientific Trends, 2022)
The article presents the dependence of field germination, duration of germination and viability of millet seeds as a repeated crop on the field vacated by autumn soft wheat harvest, depending on different planting methods and standards. Germination of replanted millet variety "Saratovskaya-853" in 7 days when planted without tillage, 8 days in row planting and plowing options, plant viability 78.6-83.4% in plowed planting option, 76.2-83% in row planting option, 2%, it was determined to be 81.5-86.8% in the no-till option.
Keywords: Kuzgi grain with spikes, Saratovskaya-853, seed, germination, fertility, viability